Agricultural technology adoption and deforestation: Evidence from a randomized control trial - Bloem, Jeffrey R.; Lundberg, Clark (Elsevier, 2026)
We study the effect of the adoption of improved agricultural inputs on deforestation using a randomized control trial in Nigeria which introduced a more efficient and environmentally-friendly nitrogen fertilizer. We combine survey data from the intervention with earth observation data to develop a generalizable method for evaluating the effects of cluster-level interventions on landscape-level outcomes. We find evidence of an intensification response to treatment exposure that reflects significant heterogeneity across land cover. On land with relatively sparse pre-intervention tree cover, treatment exposure increased deforestation while in denser forest areas the intervention reduced deforestation. We find corresponding effects showing treatment exposure increases agricultural productivity. Our results reflect an intensification response to improved agricultural technology that redirects agricultural activity away from forests and towards existing cropland.